Cervical intraepithelial neoplasia in a cohort of HIV-positive women at the University Hospital of the West Indies: management and outcome - Bambury, I; Mullings, A; Fletcher, H; Johnson, N; Tolluch-Reid, M (West Indian medical journal, 2013)
To determine the rate of recurrence of cervical intraepithelial neoplasia (CIN) in HIV-positive women evaluated at the University Hospital of the West Indies (UHWI). A chart review of all non-pregnant HIV-positive women who attended the gynaecologic and colposcopic clinics between January 1994 and December 2004 identified 21 such women. Fifteen of these patients who had CIN and had at least one follow-up Pap smear were the main subjects of this study. These patients were compared to 21 HIV-negative controls who were seen during the same period and who also had at least one follow-up Pap smear. Treatment modalities for the groups included cold coagulation and large loop excision of the transformation zone (LLETZ). Cox proportional hazards analysis was used to determine the effect of HIV status on the time to first recurrence of CIN. The mean ages of the subjects were 32.7 ± 8.0 and 33.2 ± 8.1 years, respectively. With a mean follow-up period of 1.7 years, the rate of recurrence of CIN in patients with and without HIV was 66.24 (95% CI 27.6, 159.1) and 3.0 (95% CI 1.3, 7.3) per 100 person years. The hazards rate ratio for recurrence in subjects with HIV after adjusting for age and CIN stage was 19.1 (95% CI 4.4, 82.1). HIV increases the risk of recurrence of CIN.